2005
DOI: 10.1007/s00414-005-0546-8
|View full text |Cite
|
Sign up to set email alerts
|

Y-STR typing of an Austrian population sample using a 17-loci multiplex PCR assay

Abstract: Y-chromosomal STR haplotypes were determined from a sample of 135 unrelated men and 70 sons from Tirol (Austria) using the AmpFlSTR Yfiler PCR amplification kit (Applied Biosystems) that coamplifies 17 YSTRs. The panel of markers includes the 9-loci European minimal haplotype (minHt) and, in addition, the markers DYS437, DYS438, DYS439, DYS448, DYS456, DYS458, DYS635 (Y GATA C4) and Y GATA H4. A total of 130 different haplotypes (125 were unique) were identified by the 17 Y-STR markers, an increase of 19 compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
6

Year Published

2005
2005
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 21 publications
(22 reference statements)
5
28
6
Order By: Relevance
“…Paternity was confirmed by the paternity index value of 5.2 Â 10 3 for 45A and 2.6 Â 10 3 for 52A in the Asian population when the mothers' alleles are included. Thus far, in the four other published studies describing mutation rates with the 17 Yfiler loci [5][6][7][8] there have been no reports of a double mutation or a two repeat loss within a single father/son sample pair. However, previous studies involving fewer Y-STR loci have identified more than one mutation in a father/son pair.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Paternity was confirmed by the paternity index value of 5.2 Â 10 3 for 45A and 2.6 Â 10 3 for 52A in the Asian population when the mothers' alleles are included. Thus far, in the four other published studies describing mutation rates with the 17 Yfiler loci [5][6][7][8] there have been no reports of a double mutation or a two repeat loss within a single father/son sample pair. However, previous studies involving fewer Y-STR loci have identified more than one mutation in a father/son pair.…”
Section: Resultsmentioning
confidence: 99%
“…In Table 3, we report the most current mutation rate information available on the 17 Y-STR loci in the Yfiler TM kit, as this will be important for laboratories using this technology. The final mutation rates for the Y-STR loci were determined by pooling the data in this study with mutation rate data provided by the Y Chromosome Haplotype Reference Database (YHRD) www.YHRD.org, published articles and papers in press [5][6][7][8][13][14][15][16][17]. Haplotype information for the 778 samples considered in this study across the 17 Yfiler loci is available in Supplementary material in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the shared haplotypes were very well represented (H18-7.9%; H21-15.9% and H24-13.5%) reaching unusually high values in comparison to those found in most populations for lineages defined by such a high number of Y-STRs (e.g. Alves et al 2007;Turrina et al 2006;Berger et al 2005;Soltyszewski et al 2007). In most European populations haplotype diversity is higher than 99.9%, in contrast with the low value now detected in the Portuguese Gypsies (0.9437 ± 0.0107).…”
Section: Y-str Haplotype Diversitymentioning
confidence: 88%
“…Therefore, alternative techniques need to be applied. For instance, deficiency cases can be solved by sequence analysis of the mitochondrial control region or by analysis of Y-chromosome and X-chromosome specific STRs [4,7,19,26,27]. If only highly degraded DNA is available for analysis, typing of single nucleotide polymorphisms (SNPs) can be the method of choice [24].…”
Section: Introductionmentioning
confidence: 99%